Recent trends in managing abnormal uterine bleeding - Ananthula, Shruthi; Gopalan, Ushadevi; Kumarapillai, Sivan Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Abnormal uterine bleeding is one of the most common problems among women of reproductive age. It is an important health care problem and may cause physiological as well as psycological stress impairing the quality of life. The aim of this review was to present various management options for women suffering from menorrhagia. An extensive electronic literature search was done using search engines like PubMed and Google scholar using the mesh terms/ key words like “abnormal uterine bleeding, menorrhagia, medical management, hysterectomy” to identify trials and reviews on management of abnormal uterine bleeding. Various pharmacological and surgical treatment options are available, among medical therapy Tranexamic acid being most effective. Second-generation endometrial ablation techniques are effective and safe alternatives compared to first-generation devices. Hysterectomy should be considered as a last resort in management of AUB as this major surgery is associated with high morbidity and mortality rates. Thus role of clinician is to counsel every women and provide full information regarding both medical as well as surgical treatment modalities available and facilitate them in making an appropriate choice.